The NF‐κB inhibitor SC75741 efficiently blocks influenza virus propagation and confers a high barrier for development of viral resistance. (5th February 2013) - Ehrhardt, Christina; Rückle, Andrea; Hrincius, Eike R.; Haasbach, Emanuel; Anhlan, Darisuren; Ahmann, Katharina; Banning, Carina; Reiling, Sarah J.; Kühn, Joachim; Strobl, Stefan; Vitt, Daniel; Leban, Johann; et al.
Summary Ongoing human infections with highly pathogenic avian H5N1 viruses and the emergence of the pandemic swine‐origin influenza viruses (IV) highlight the permanent threat elicited by these pathogens. Occurrence of resistant seasonal and pandemic strains against the currently licensed antiviral medications points to the urgent need for new and amply available anti‐influenza drugs. The recently identified virus‐supportive function of the cellular IKK/NF‐κB signalling pathway suggests this signalling module as a potential target for antiviral intervention. We characterized the NF‐κB inhibitor SC75741 as a broad and efficient blocker of IV replication in non‐toxic concentrations. The underlying molecular mechanism of SC75741 action involves impaired DNA binding of the NF‐κB subunit p65, resulting in reduced expression of cytokines, chemokines, and pro‐apoptotic factors, subsequent inhibition of caspase activation and block of caspase‐mediated nuclear export of viralribonucleoproteins. SC75741 reduces viral replication and H5N1‐induced IL‐6 and IP‐10 expression in the lung of infected mice. Besides its virustatic effect the drug suppresses virus‐induced overproduction of cytokines and chemokines, suggesting that it might prevent hypercytokinemia that is discussed to be an important pathogenicity determinant of highly pathogenic IV. Importantly the drug exhibits a high barrier for development of resistant virus variants. Thus, SC75741‐derived drugs may serve as broadly non‐toxic anti‐influenza agents.